2011
DOI: 10.1002/dev.20608
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' responses to children's negative emotions and child emotion regulation: The moderating role of vagal suppression

Abstract: The current study examined the moderating effect of children’s cardiac vagal suppression on the association between maternal socialization of negative emotions (supportive and non-supportive responses) and children’s emotion regulation behaviors. One hundred and ninety-seven 4-year-olds and their mothers participated. Mothers reported on their reactions to children’s negative emotions and children’s regulatory behaviors. Observed distraction, an adaptive self-regulatory strategy, and vagal suppression were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 59 publications
(57 reference statements)
7
97
2
2
Order By: Relevance
“…Specifically, parents' supportive contingent reactions are associated with greater observed spontaneous expression of a range of emotions (Fabes et al, 2002), less intense observed negative affect during emotionally arousing events (e.g., being separated from their mothers; Denham, 1993), and higher parent-ratings of emotion regulation skills in preschoolers (Perry et al, 2011). These findings suggest that parents' supportive contingent reactions are associated with TD preschoolers' more effective emotion regulation during distressing events and greater comfort exploring and expressing a broader range of positive and negative emotions.…”
Section: Contingent Reactions To Children's Emotions In Td Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, parents' supportive contingent reactions are associated with greater observed spontaneous expression of a range of emotions (Fabes et al, 2002), less intense observed negative affect during emotionally arousing events (e.g., being separated from their mothers; Denham, 1993), and higher parent-ratings of emotion regulation skills in preschoolers (Perry et al, 2011). These findings suggest that parents' supportive contingent reactions are associated with TD preschoolers' more effective emotion regulation during distressing events and greater comfort exploring and expressing a broader range of positive and negative emotions.…”
Section: Contingent Reactions To Children's Emotions In Td Populationmentioning
confidence: 99%
“…Not surprisingly, research and theory indicate that parents' supportive reactions to their children's negative emotions are related to TD children's more adaptive emotional expressivity, understanding, and regulatory skills (e.g., Denham, Zoller, & Couchoud, 1994b;Fabes et al, 2002;Perry et al, 2011), whereas nonsupportive reactions are related to poorer EC abilities (e.g., Denham, Mitchell-Copeland, Stranberg, Auerbach, & Blair, 1997;Fabes et al, 2002;Perry et al, 2011). Specifically, parents' supportive contingent reactions are associated with greater observed spontaneous expression of a range of emotions (Fabes et al, 2002), less intense observed negative affect during emotionally arousing events (e.g., being separated from their mothers; Denham, 1993), and higher parent-ratings of emotion regulation skills in preschoolers (Perry et al, 2011).…”
Section: Contingent Reactions To Children's Emotions In Td Populationmentioning
confidence: 99%
See 3 more Smart Citations